"z_{xx} + 2z_{xy} + z_{yy} = 0\\\\\n\n\\frac{\\partial^2 z}{\\partial x^2} + 2\\frac{\\partial^2 z}{\\partial x \\partial y} + \\frac{\\partial^2 z}{\\partial y^2} = 0\\\\\n\n\\left(\\frac{\\partial }{\\partial x} + \\frac{\\partial }{\\partial y}\\right)^2 z = 0\\\\\n\n\\implies \\frac{\\partial z}{\\partial x} + \\frac{\\partial z}{\\partial y} = 0\\\\\n\n\\implies \\frac{\\mathrm{d}y}{\\mathrm{d}x} = -1\\\\\n\n\\implies y = -x + C, \\,\\, y + x = C\\\\\n\n\\implies z = F(y + x)"
Comments
Leave a comment